Zee model with quasidegenerate neutrino masses and where to find it - R. Primulando; J. Julio; P. Uttayarat (European Physical Journal C: Particles and Fields, 2022)
Abstract We present a Zee model with a family dependent $$Z_2$$ Z 2 symmetry for radiative neutrino masses. Our motivation is to get a model that correctly describes neutrino oscillation phenomena, while at the same time offers definite predictions. The imposed $$Z_2$$ Z 2 symmetry greatly reduces the number of free parameters in the model. These parameters are then determined from the neutrino data, from which one can study its outcomes. Our setup only admits quasidegenerate neutrino masses with the sum of neutrino masses between 100 and 130 meV, the effective Majorana mass between 20 and 40 meV, and the effective electron neutrino mass between 48 and 53 meV. The ratio of the vacuum expectation values of the Higgs doublets, $$\tan β $$ tan β , is found to be $$\tan β \lesssim 0.5$$ tan β ≲ 0.5 and $$\tan β \gtrsim 10$$ tan β ≳ 10 . The former is ruled out by lepton flavor violation (LFV) processes, such as $$μ → eγ $$ μ → e γ and $$μ → e$$ μ → e conversion, which are determined up to two loops. For the latter, these LFV processes are within reach of the next generation of experiments. Moreover, for $$\tan β \gtrsim 10$$ tan β ≳ 10 , the couplings of heavy neutral scalars to dimuon are significant. If they are sufficiently light, i.e., $$\lesssim 200$$ ≲ 200 GeV, collider search for their decays into muon pair provides a stronger constraint on most parts of the model parameter space than the LFV ones.